Respuesta :
Step-by-step explanation:
First, distribute the outside numbers into the parentheses:
5*x+5*-12+6=3*2x+3*-7
5x-60+6=6x-21
Combine like terms
5x-54=6x-21
Add 21 to both sides
5x-33=6x
Subtract 5x from both sides
you wind up getting x=-33
x=-33
you can check to make sure that's the correct answer but simply plugging in -33 for x and checking to make sure both sides of the equation are equal:
-33-12=-45*5=-225+6=-219
-33*2=-66-7=-73*3=-219
So, yes, x equals -33
you distribute the 5 and times it by x and -12 then the problem would look like this
5x-60+6=3(2x-7)
next you distribute the 3 and times it with 2x and -7 then the problem would look like this
5x-60+6=6x-21
then you solve by combining like terms on the left so you minus 6 from 60 and get 54 so now you have
5x-54=6x-21
now you add 54 to -21 but since it’s a negative you will subtract and take the larger numbers side which will be 33
now you have a problem that looks like this
5x=6x+33
so now you subtract 6x with 5x and get 1x
so the problem will look like this
1x= 33
then you divide 1x on both sides and the answer is
x = 33
5x-60+6=3(2x-7)
next you distribute the 3 and times it with 2x and -7 then the problem would look like this
5x-60+6=6x-21
then you solve by combining like terms on the left so you minus 6 from 60 and get 54 so now you have
5x-54=6x-21
now you add 54 to -21 but since it’s a negative you will subtract and take the larger numbers side which will be 33
now you have a problem that looks like this
5x=6x+33
so now you subtract 6x with 5x and get 1x
so the problem will look like this
1x= 33
then you divide 1x on both sides and the answer is
x = 33